Quality Education through Standards: Model Primary School Standards (MPSS) and Student Learning Outcomes in Cambodian Primary Schools - Tang, Theara; Ret, Thearom (Philippine Social Science Journal, 2025)
Aligned with Cambodia’s Education Strategic Plan 2024–2028, this study examines the relationship between the Model Primary School Standards (MPSS) framework and student learning outcomes. Utilizing a qualitative design involving focus groups and interviews with 52 stakeholders in Pailin province, the research identified seven core factors facilitating implementation success, revealing that MPSS improves learning through enhanced instructional quality, school-community collaboration, and effective leadership. While resource limitations and varying engagement levels remain challenges, the findings underscore the efficacy of standards-based, context-responsive reforms. Consequently, this study offers practical recommendations for policymakers and lays the groundwork for future quantitative and comparative research to evaluate the program’s long-term sustainability and nationwide scalability.